Establishing peat-forming plant communities: A comparison of wetland reclamation methods in Alberta's oil sands region ... - Borkenhagen, Andrea; Cooper, David; House, Melissa; Vitt, Dale (Dryad, 2023)
The Sandhill Wetland (SW) and Nikanotee Fen (NF) are two wetland research projects designed to test the viability of peatland reclamation in the Alberta oil sands post-mining landscape. To identify effective approaches for establishing peat-forming vegetation in reclaimed wetlands, we evaluated how plant introduction approaches and water level gradients influence species distribution, plant community development, and establishment of bryophyte and peatland species richness and cover. Plant introduction approaches included seeding with a Carex aquatilis-dominated seed mix, planting C. aquatilis and J. balticus seedlings, and spreading a harvested moss layer transfer. Establishment was assessed six years after introduction at SW and five years after introduction at NF. A total of 51 species were introduced to the reclaimed wetlands, and 122 species were observed after five and six years. The most abundant species in both reclaimed wetlands was C. aquatilis, which produced dense canopies and occupied the ... : Study Region The Sandhill Wetland (SW) and Nikanotee Fen (NF) are located north of Fort McMurray, Alberta, Canada. Mean total annual precipitation in Fort McMurray is 419 mm, with mean annual rainfall of 316 mm and snowfall of 134 cm. Daily mean temperatures dip to -17.4o C in January and peak at 17.1o C in July (1981-2010 climate normal from weather station at 56° 39’ N, 111° 13’ W; Environment Canada 2018a). The data reported here were collected in the summer of 2017, when total annual precipitation was 312 mm and daily mean July temperature averaged 22.9o C. (daily data report for 2017 from weather station at 56° 39’ N, 111° 13’ W; Environment Canada 2018b). Vegetation Sampling Vegetation composition was sampled and depth to water measured in 79 plots at SW and 42 plots at NF in July 2017. Canopy cover by species was assessed by visual estimation to the nearest 5 % in an 8 m2 circular plot at SW and to the nearest 1 % in a 4 m2 square plot at NF. The sampled area represents 0.37% of the total wetland area ...